2023
DOI: 10.3390/ijerph20227065
|View full text |Cite
|
Sign up to set email alerts
|

Association between Japanese Diet Adherence and Muscle Weakness in Japanese Adults Aged ≥50 Years: Findings from the JSTAR Cohort Study

Akio Shimizu,
Kiwako Okada,
Yasutake Tomata
et al.

Abstract: Japanese diet adherence has been inversely correlated with muscle weakness. In this study, we aimed to validate that association. Longitudinal data from 1699 individuals aged ≥50 years (mean age 62.5 ± 6.9 years, 50.4% female) at two time points (2007 and 2011) were used. Participants without muscle weakness from several regions in Japan were included. The 12-component revised Japanese Diet Index (rJDI12) classified by tertiles assessed adherence to the Japanese dietary pattern. Muscle weakness was defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Domoto et al reported that taurine, one of the nutrients found in seaweed and seafood, is inversely correlated with lower extremity muscle strength. Previous studies have reported that adherence to the Japanese dietary pattern is protective against declining muscle strength ( 2 ) and mobility capacity ( 3 ) in the older population. According to Domoto et al , adherence to the Japanese dietary pattern preserves muscle health, which may be related to a high intake of taurine.…”
mentioning
confidence: 99%
“…Domoto et al reported that taurine, one of the nutrients found in seaweed and seafood, is inversely correlated with lower extremity muscle strength. Previous studies have reported that adherence to the Japanese dietary pattern is protective against declining muscle strength ( 2 ) and mobility capacity ( 3 ) in the older population. According to Domoto et al , adherence to the Japanese dietary pattern preserves muscle health, which may be related to a high intake of taurine.…”
mentioning
confidence: 99%